(untitled) (Applied Biological Research, 2023)
Induced mutagenesis has been effectively demonstrated as one of the best possible methodology for the genetic improvement of crop species. Egyptian clover (Trifolium alexandrinum L.), an important green fodder plant species of the family Fabaceae with immense agricultural value, was selected for the present study to improve its genetics by using the strategy of induced mutagenesis. Dry and healthy seeds of Egyptian clover cv. ‘Wardan’ were exposed to different doses (0.1, 0.3 and 0.5%) of Ethyl methane sulphonate (EMS) for variable time (3 and 5 h). The germination and survival percentages were recorded in M1 generation and 0.3% EMS at 5 h was determined as LD50 dose; whereas frequency of chlorophyll mutants and viable mutants along with cytological observations were screened in M2 generation. A broad spectrum of chlorophyll and viable mutants with different frequencies were observed. Cytological abnormalities increased along with rising EMS concentrations and mutagen exposure time. The findings are encouraging and show that significant genetic variability had been induced by EMS. Thus, tcomprehensive selection of the desirable mutants may bring about advancement of improved and high yielding mutants of T. alexandrinum in upcoming generation.